1996
DOI: 10.1093/carcin/17.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of transforming growth factor-α and epidermal growth factor receptor, but not epidermal growth factor, in exocrine pancreatic tumours in hamsters

Abstract: Using immunohistochemistry, Northern blotting and a semi-quantitative PCR technique, epidermal growth factor (EGF), transforming growth factor-alpha (TGF-alpha) and epidermal growth factor receptor (EGFR) expression were studied in the pancreas of N-nitrosobis(2-oxopropyl)-amine (BOP)-treated hamsters. After initiation pancreatic carcinogenesis was modulated by a high fat diet or by injections with the cholecystokinin analogue caerulein. Autopsies were performed 6 and 12 months after the last injection with BO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Pancreatic cancer is the fourth leading cause of cancerrelated death in the United States, and nearly all patients diagnosed with pancreatic cancer die from a cancer-related death (24,26,52), with a 3% 5-year survival rate following diagnosis (43). Metastases are common in the process, particularly to the lymph nodes and liver (9,19,61). Histopathological analysis shows a ductal histology that makes up Ͼ90% of the cases of pancreatic adenocarcinoma (50).…”
mentioning
confidence: 99%
“…Pancreatic cancer is the fourth leading cause of cancerrelated death in the United States, and nearly all patients diagnosed with pancreatic cancer die from a cancer-related death (24,26,52), with a 3% 5-year survival rate following diagnosis (43). Metastases are common in the process, particularly to the lymph nodes and liver (9,19,61). Histopathological analysis shows a ductal histology that makes up Ͼ90% of the cases of pancreatic adenocarcinoma (50).…”
mentioning
confidence: 99%
“…Correspondingly, PanIN lesions in a murine model of pancreatic cancer expressed TGFα, but not EGF. 42 In vitro experiments utilizing acinar explants revealed that TGFα-mediated EGFR activation promoted ADM via a Notch-dependent mechanism. 43,44 Additionally, expression of KRAS G12D promotes ADM both in vitro and in vivo, via an EGFR-dependent mechanism.…”
Section: Egfr and The Development Of Pancreatic Cancermentioning
confidence: 99%
“…All animals were given standard laboratory chow until one week after the last injection. From that time onwards, AIN-76-based diets were provided (Visser et al, 1995(Visser et al, , 1996. All carcinogen-treated animals were assigned randomly to one of the following experimental sub-groups: regular diet (5% corn oil); regular diet plus s.c. injections of 2.5 µg/kg body weight caerulein, 3 times a week, or high-fat diet (20% corn oil), in isocaloric (rat) or non-isocaloric (hamster) form (Birt et al, 1989).…”
Section: Animalsmentioning
confidence: 99%